2008
DOI: 10.1529/biophysj.107.114447
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Diffusion and Binding Kinetics by Contact Area FRAP

Abstract: The immunological synapse is a stable intercellular structure that specializes in substance and signal transfer from one immune cell to another. Its formation is regulated in part by the diffusion of adhesion and signaling molecules into, and their binding of countermolecules in the contact area. The stability of immunological synapses allows receptor-ligand interactions to approximate chemical equilibrium despite other dynamic aspects. We have developed a mathematical model that describes the coupled reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 38 publications
(67 reference statements)
5
80
0
Order By: Relevance
“…Photobleaching measurements showed that CD4/pMHC II binding is reversible, and that the mobility of CD4 in the contact is more than 10-fold lower compared with outside the contact. Although the 2D off-rate (k off ) for the CD4/pMHC II interaction could not be determined in the present experiments, it can be estimated to be of the order of 250 s , which is comparable to that measured for protein-protein interactions of higher affinity between T cells and APCs (13,29). However, the k off is orders of magnitude larger (12,13,29).…”
Section: Discussionmentioning
confidence: 42%
“…Photobleaching measurements showed that CD4/pMHC II binding is reversible, and that the mobility of CD4 in the contact is more than 10-fold lower compared with outside the contact. Although the 2D off-rate (k off ) for the CD4/pMHC II interaction could not be determined in the present experiments, it can be estimated to be of the order of 250 s , which is comparable to that measured for protein-protein interactions of higher affinity between T cells and APCs (13,29). However, the k off is orders of magnitude larger (12,13,29).…”
Section: Discussionmentioning
confidence: 42%
“…From then on, many experimental assays have been developed by coordinating the biological experiments and mechanical measurements. These include micropipette aspiration [25,31,36,51], optical tweezers [37,52,53], biological force probes [45,[54][55][56], atomic force microscopy (AFM) [38,39,43,[57][58][59][60][61], flow chamber [62][63][64][65], microcantilever needle [28], centrifugation [66], rosetting [67], cone-plate viscometer [68,69], surface force apparatus [70,71], and fluorescence recovery after photobleaching (FRAP) [72,73]. Here, two assays of micropipette aspiration and atomic force microscopy are exemplified to demonstrate how they work.…”
Section: Experimental Approaches For Quantifying 2d Kinetics and Forcmentioning
confidence: 99%
“…FRAP (Fluorescence Recovery After Photobleaching) is a method for the diffusion kinetics (and also, correctly, reaction-diffusion kinetics) measurements in living cells using fluorescence microscopy (Zlatanov, 1987;Lopez, 1988;Swaisgood, 1989; Anders, 1990;Nagy, 1990; Bryers, 1998;Salomé, 1998;Tinland, 1998;Higgs, 2000;Reits, 2001;Carrero, 2003;Cha 2004;Joubert, 2004;Fukano, 2004;James, 2004;Sprague, 2005;Lele, 2006;Abbaci, 2007;Febo-Ayala, 2007;Travascio, 2007;Dushek, 2008;Kang, 2008;McNally, 2008;Tolentino, 2008;Lambert, 2009;Travascio, 2009; Hagman, 2010;Mueller, 2010;Mai, 2011;Wachsmuth, 2014;Yapp, 2016) which allows to estimate quantitatively the two dimensional lateral diffusion in molecularly thin film containing fluorescent-labeled probes, or for single cell examination (i.e. the study of lateral mobility of cellular molecules).…”
Section: Introductionmentioning
confidence: 99%